2010
DOI: 10.1121/1.3488675
|View full text |Cite
|
Sign up to set email alerts
|

Build-up of the tendency to segregate auditory streams: Resetting effects evoked by a single deviant tone

Abstract: The tendency to hear a sequence of alternating low (L) and high (H) frequency tones as two streams can be increased by a preceding induction sequence, even one composed only of same-frequency tones. Four experiments used such an induction sequence (10 identical L tones) to promote segregation in a shorter test sequence comprising L and H tones. Previous studies have shown that the build-up of stream segregation is usually reduced greatly when a sudden change in acoustic properties distinguishes all of the indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
78
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(88 citation statements)
references
References 29 publications
9
78
1
Order By: Relevance
“…Consistent with this idea, Haywood & Roberts [22] showed that a single deviant tone (a change in frequency, duration or replacement with silence) at the end of an induction sequence can lead to substantial resetting of build-up. They proposed that a single change actively resets the build-up evoked by the induction sequence.…”
Section: The Build-up Resetting and Decay Of Stream Segregation (A)mentioning
confidence: 58%
“…Consistent with this idea, Haywood & Roberts [22] showed that a single deviant tone (a change in frequency, duration or replacement with silence) at the end of an induction sequence can lead to substantial resetting of build-up. They proposed that a single change actively resets the build-up evoked by the induction sequence.…”
Section: The Build-up Resetting and Decay Of Stream Segregation (A)mentioning
confidence: 58%
“…The process of perception changing from one stream to two streams with longer sequences is called buildup and has been attributed to adaptation of frequency-tuned neurons in the brainstem and the auditory cortex (Micheyl, Tian, Carlyon, & Rauschecker, 2005;Pressnitzer, Sayles, Micheyl, & Winter, 2008). Consistent with the idea of adaptation of frequencytuned neurons causing buildup is the finding that a preceding sequence of single-frequency tones that match the frequency of A or B tones can facilitate streaming (Beauvois & Meddis, 1997;Haywood & Roberts, 2010;Rogers & Bregman, 1993).…”
mentioning
confidence: 93%
“…It is therefore possible that only relatively large stimulus changes trigger a perceptual reset. However, Haywood & Roberts [64] found perceptual reset with a change (deviation) of only three semitones, and Anstis & Saida [55], presenting frequency-modulated tones, observed a reset with a change of two semitones from the centre of adaptation. Thus, the requirement of large stimulus change is doubtful.…”
Section: Review Multistability In Auditory Streaming I Winkler Et Amentioning
confidence: 99%
“…Previous studies [36,55,[64][65][66] have consistently reported perceptual reset (i.e. a restart from the state at the outset dominated by the integrated percept, with the necessity to gather evidence for the segregated organization anew) when parameter changes were introduced in the auditory streaming paradigm.…”
Section: Review Multistability In Auditory Streaming I Winkler Et Amentioning
confidence: 99%